2021
DOI: 10.1136/bmjopen-2020-042948
|View full text |Cite
|
Sign up to set email alerts
|

Access to oxytocin and misoprostol for management of postpartum haemorrhage in Kenya, Uganda and Zambia: a cross-sectional assessment of availability, prices and affordability

Abstract: ObjectiveTo assess access (availability and affordability) to oxytocin and misoprostol at health facilities in Kenya, Uganda and Zambia to improve prevention and management of postpartum haemorrhage (PPH).DesignThe assessment was undertaken using data from Health Action International (HAI) research on sexual and reproductive health commodities based on a cross-sectional design adapted from the standardised WHO/HAI methodology.SettingData were collected from 376 health facilities in in Kenya, Uganda and Zambia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…These policies have led to significant increases in the rate of facility-based delivery [13,14], despite several challenges in implementation that affected access for some potential beneficiaries [15]. There have also been significant efforts to scale up effective interventions for PPH prevention and treatment in health facilities in Kenya including training health care providers on Active Management of the Third Stage of Labor and increasing the coverage of effective uterotonic medicatoins [16,17]. However, mortality from PPH remains high despite these efforts and a recent review of maternal mortality in Kenya identified quality of care as a key challenge [18].…”
Section: Introductionmentioning
confidence: 99%
“…These policies have led to significant increases in the rate of facility-based delivery [13,14], despite several challenges in implementation that affected access for some potential beneficiaries [15]. There have also been significant efforts to scale up effective interventions for PPH prevention and treatment in health facilities in Kenya including training health care providers on Active Management of the Third Stage of Labor and increasing the coverage of effective uterotonic medicatoins [16,17]. However, mortality from PPH remains high despite these efforts and a recent review of maternal mortality in Kenya identified quality of care as a key challenge [18].…”
Section: Introductionmentioning
confidence: 99%